#TITLE_ALTERNATIVE# - MAHENDRA WIJAYA (NIM 23205044), ADRIANTO
Synchronized Multimedia Integration Language (SMIL) is a language as tools for doing integration between several type of multimedia files. As an example, SMIL can be used to as a tool in presentation activities manaagement system, like a symposium, to create a multimedia presentation. This research have main objectives to design a multimedia presentation system based on web application and Synchronized Multimedia Integration Language (SMIL). This process of design using model-view-controller (MVC) concept to be implemented. The design also have prepared for specifict framework that alread developed by community in the internet. The other objectives of this research is doing a capacity planning to prepare the implementation of web application that have designed. A stocastic model have been developed and used to modeling the relation of response time and number of user. This model can be used to explain how the effect of duplication system and the increasing of the capacity.